Assessing strategic, tactical, and operational decision-making and risk in a livestock production chain through experimental simulation platforms - Koliba, Christopher; Merrill, Scott C.; Zia, Asim; Bucini, Gabriela; Clark, Eric; Shrum, Trisha R.; Wiltshire, Serge; Smith, Julia M. (Frontiers in Veterinary Science, 2022)
This paper provides a research summary of a series of serious games and simulations that form the basis of an experimental platform for the study of human decision-making and behavior associated with biosecurity across complex livestock production chains. This platform is the first of its kind to address the challenges associated with scaling micro- behavior of biosecurity decision-making to macro- patterns of disease spread across strategic, tactical and operational levels, capturing the roles that facility managers and front-line workers play in making biosecurity decisions under risk and uncertainty. Informational and incentive treatments are tested within each game and simulation. Behavioral theories are used to explain these findings. Results from serious games in the form of behavioral probability distributions are then used to simulate disease incidence and spread across a complex production chain, demonstrating how micro-level behaviors contribute to larger macro-level patterns. In the case of this study, the propensity to adopt micro-level biosecurity practices are applied to a network percolation disease spread model. By presenting the suite of companion models of behavior and disease spread we are able to capture scaling dynamics of complex systems, and in the process, better understand how individual behaviors impact whole systems.